Alliance’s research and engagement contributes to developing national action plan for transparent, responsible, and sustainable food systems transformation in Vietnam - Huynh Thi Thanh Tuyen (2023)
Alliance successfully integrated the concepts of sustainable healthy diets and sustainable food systems into the Q&A guidelines for the Strategy for Sustainable Agriculture and Rural Development, Period 2021–2030 and Vision to 2050 led by IPSARD-MARD. Since 2021, Alliance researchers have engaged in the process of UNFSS dialogues and summit, and technical meetings for drafting the technical report highlighting the government’s need for a food systems’ plan and developing the National Action Plan for Transparent, Responsible, and Sustainable Food Systems Transformation (2022–2030) which was approved by the Prime Minister level (March 2023) and is critical to the Strategy’s implementation.